RANCANG BANGUN APLIKASI ABSENSI GURU DAN STAF TU DENGAN PENERAPAN GEOLOCATION DAN FINGERPRINT BERBASIS ANDROID DI SMK GKE MANDOMAI - Berkati, Axel; Licantik; Nugrahaningsih, Nahumi; Lestari, Ariesta; Sylviana, Felicia (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2024)
Attendance is one of the work assessments and as proof of attendance is very important. At this time, the attendance system used by SMK GKE Mandomai is still implementing a manual attendance system, which is every day to sign at every date of entry to work, and attendance is done 2 times, namely entry attendance and return attendance. This manual attendance system has the potential to cause some problems, such as attendance papers that are easily lost or scattered and the possibility of manipulating attendance data. As a solution, namely by designing an attendance application with the application of geolocation and fingerprint on android as security when doing absences, in order to prevent teachers and TU staff who are outside the school location to fill absences. The development method used in designing this system is the Waterfall model with its stages, namely Software Requirements Analysis, Design, Coding, and testing. System design using UML model, implement coding using JavaScript, React Native framework and React JS, backend using Firebase. the results of this system design, produce Android-based attendance system for teachers and staff TU attendance in school areas.